Response to "Antiviral RNA silencing in mammals: the importance of selecting the appropriate experimental model" - Svoboda, Petr; Malik, Radek (Nucleic acids research, 2025)
In their commentary Antiviral RNA silencing in mammals: the importance of selecting the appropriate experimental model, Xing Liu and Yang Li critically review our recent work by Kulmann et al. published in Nucleic Acids Research. While we agree with authors on a number of their points, especially those concerning complexity of virus-host systems, we would like to add some missing information and clarify several important aspects of our animal model system and mammalian canonical RNA interference in general.
Keywords: malá interferující RNA; Mammals; Humans; zvířata; RNA interference; lidé; RNA, Small Interfering; savci; Animals; RNA Interference